Selection of Ionic Liquids to be Used as Separation Agents for Terpenes and Terpenoids - Martins, Monia A. R.
In this work, ionic liquids are evaluated for the first time as solvents for extraction and entrainers in separation processes involving terpenes and terpenoids. For that purpose, activity coefficients at infinite dilution, gamma(infinity)(13), of terpenes and terpenoids, in the ionic liquids [C(4)mim]Cl, [C(4)mim][CH3SO3], [C(4)mim][(CH3)(2)PO4] and [C(4)mim][CF3SO3] were determined by gas liquid chromatography at six temperatures in the range 398.15 to 448.15 K On the basis of the experimental values, a correlation of gamma(infinity)(13) with an increase of the solubility parameters is proposed. The infinite dilution thermodynamic functions were calculated showing the entropic effect is dominant over the enthalpic. Gas liquid partition coefficients give indications about the recovery and purification of terpenes and terpenoids from ionic liquid solutions. Presenting a strong innovative character, COSMO-RS was evaluated for the description of the selectivities and capacities, showing to be a useful tool for the screening of ionic liquids in order to find suitable candidates for terpenes and terpenoids extraction, and separation. COSMO-RS predictions show that in order to achieve the maximum separation efficiency, polar anions should be used such as bis(2,4,4-trimethylpentyl)phosphinate or acetate, whereas high capacities require nonpolar cations such as phosphonium.